A scholar and man of honour, humility, and devotion: a tribute to Professor Dr. Jamil Farooqui - Md Noon, Hazizan (Department of Communication, KIRKHS, IIUM, 2024)
The article is a homage to the late Professor Dr. Jamil Farooqui, a respected former colleague at the Department of Sociology and Anthropology, IIUM. Prof. Jamil was known for his expertise in Sociological Perspectives, Research Methodology, and Islamic Sociology, and had a significant impact on teaching and research at IIUM. The piece includes a list of Prof. Jamil’s publications and discusses his efforts to integrate Islamic perspectives into sociology. Colleagues share their memories, highlighting Prof. Jamil’s humility, kindness, and role as a mentor and friend.